Strategies for Realizing Teacher Creativity in Utilizing AI-Based Learning Media in Elementary Schools - Yunita Nur Rahmawati; Achadi Budi Santosa; Dian Hidayati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Utilization of Artificial Intelligence(AI) in learning demands teacher creativity so that learning media are more effective and appropriate to the characteristics of elementary school students. This study aims to analyze strategies for realizing teacher creativity in utilizing AI-based learning media in elementary schools. This study used a qualitative approach with a case study type conducted in one of the Muhammadiyah elementary schools. The research subjects consisted of four teachers who actively utilize AI in learning. Data were collected through semi-structured interviews, participant observation, and documentation studies. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion. The results show that teacher creativity is manifested through pedagogical understanding of AI as a learning tool, planning contextual AI use, implementing AI-based active learning, and continuous evaluation of student responses and engagement. The use of AI-based learning media has a positive impact on increasing student learning motivation, learning variation, and teacher work efficiency, although obstacles are still encountered, such as limited devices, internet networks, and teacher competencies. Therefore, school managerial support is needed through continuous training and the provision of supporting infrastructure so that the use of AI in learning can run optimally.